Industrial synthetic resins handbook - Flick, Ernest W. (Noyes Publications, 1991)
This book contains short product descriptions of 3,000 resins and related products from 57 manufacturers. Contents: ABS and SAN Resins; Acetal Resins; Acrylics; Alkyds; Curing Reaction Resins; Epoxy Systems & Related Products; High Solids Resins; Nylons; Phenolics; Polycarbonates; Polyesters; Polyethylenes; Polypropylenes; Polystyrenes; Polyurethanes; Rosins, Rosin Esters & Hydrocarbon Resins; Silicones; Vinyls; Miscellaneous; Suppliers' Addresses; Trade Name Index.
Includes index.
Keywords: Gums and resins, Synthetic -- Handbooks, manuals, etc.; elektronické knihy; electronic books